Analysis of beliefs about vaccine adhering against Covid-19 in a group of young Brazilians - Vagner Souza (2022)
Introduction: In the context of the COVID-19 pandemic, in addition to public health problems, we also highlight a scenario of informational disorder, marked by ideological disputes and false information about the vaccine. Objective: this article sought to analyze the beliefs of young Brazilians about the treatment of vaccines against COVID-19. The Theory of Planned Action (TAP) was used as a theoretical framework. Method: The research had the participation of 36 people, aged between 19 and 29 years (Mean = 21.66; SD = 1.99), recruited by networks of contacts. A data collection instrument included an electronic form, composed of 28 questions, 13 related to sociodemographic aspects and 15 about what they think about covid-19 vaccine compliance. To organize and analyze the data, iramuteq software was used through word cloud techniques and analysis of similitude. Results: The main results showed that the terms "hope", "necessary", "dream" and "wonderful" presented a high frequency, that is, they were allocated as central words in the narratives of the young people. In addition, it was possible to observe a link between the terms "vaccine", "virus", "death", "normal", "science" and "information", indicating that the majority of respondents adhering to vaccination against COVID-19 and evaluates this prevention measure as a necessary strategy for health promotion. On the other hand, the belief regarding the fear of the side effects of the vaccine was also evoked by the participants. Conclusion: The sample revealed that even in the face of denialism in relation to vaccination in Brazil, the research participants demonstrated favorable beliefs about immunization against COVID-19, being among the main justifications, the feeling of hope for a better future and the possibility of guaranteeing the rights of the population.